2003
DOI: 10.1080/08880010390243004
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in Kawasaki Disease: A Risk Factor for the Development of Coronary Artery Aneurysms

Abstract: The authors report on a 2-year-old boy with atypical Kawasaki disease (KD) and thrombocytopenia who developed 3 coronary artery aneurysms. The mechanism of thrombocytopenia in KD seems to be consumption coagulopathy. Review of the 30 reported cases of KD and thrombocytopenia revealed that this combination is more common in girls and in young age groups, and is associated with an increased risk of coronary artery aneurysm and myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 8 publications
0
16
1
1
Order By: Relevance
“…Known risk factors related to the development of CAL (prolonged fever, anemia, high leukocyte counts, high band counts, C-reactive protein and male gender) [25][26][27] were not found significant in our patients. Thrombocytopenia at presentation is a known risk factor in development of CAL [28] , but contrary to this, the only statistically significant risk factor related to CAL in our patients was thrombocytosis. This might again be related to delay in the referral, diagnosis and initiation of treatment as both high platelet counts and higher incidence of CAL are found in later stages of KD [29,30] .…”
Section: Discussioncontrasting
confidence: 90%
“…Known risk factors related to the development of CAL (prolonged fever, anemia, high leukocyte counts, high band counts, C-reactive protein and male gender) [25][26][27] were not found significant in our patients. Thrombocytopenia at presentation is a known risk factor in development of CAL [28] , but contrary to this, the only statistically significant risk factor related to CAL in our patients was thrombocytosis. This might again be related to delay in the referral, diagnosis and initiation of treatment as both high platelet counts and higher incidence of CAL are found in later stages of KD [29,30] .…”
Section: Discussioncontrasting
confidence: 90%
“…Thrombocytosis is a non-specific feature of KD, but thrombocytopenia can be present in 2% of HN-KD patients. 51 A total of 79% of the current 12 patients presented with thrombocytopenia. Thrombocytopenia is a risk factor for a more severe form of KD with acute myocardial infarction and CAA.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is a risk factor for a more severe form of KD with acute myocardial infarction and CAA. 51 Patients with KDSS tend to have lower hemoglobin concentration, larger proportions of immature white cell forms (bandemia), lower platelet count, higher CRP and a greater risk of consumptive coagulopathy. 3,4 Three patients presented with macrophage activation syndrome (MAS) simultaneously with KDSS, 52 and it has been suggested that KDSS and MAS could be part of the same spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Atipik hastalarda trombositopeni, lenfopeni, nötropeni ve eozinofili gibi anormallikler seyrek olarak görülebilir 10,30 . Trombositopeni, beklenmeyen ve nadir görülen bir durumdur, IVIG tedavisine direnç olabileceğini ve koroner arter anevrizma riskinin arttığını göstermektedir 12,27,54 . Trombositopenik olan altı Kawasaki hastasının toplandığı bir çalışmada, hastalara IVIG tedavisi verildikten sonra trombosit sayısının hızlıca normal değerlere döndüğü ve hastaların hepsinde trombositoz geliştiği bildirilmiştir 12 .…”
Section: Hematolojik Anormalliklerunclassified